Determinants of Food Security in Ogbomoso Agricultural Zone - *, Olaoye; Adebola, Toyin; *, Kayode; Oluwatoyin, Ajoke; *, Oladiran; Omobolanle, Joy (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
This study analyzed determinants of food security in Ogbomoso agricultural zone. Multistage random sampling technique was used in selecting the respondent for the study. A total of 148 households respondents were interviewed. Data were subjected to descriptive statistics and logit model. About 70% of the respondents were literates. The coefficient of age of household head was negative and significant at 1 per cent. However, the coefficient of income was positive at 1 per cent. Therefore, educated and young individuals should be encouraged to engage in agriculture.